Analysis of Shifting Meaning of Expressions in German Cultural Contexts - Sugiarto, Aigna Zhalfa Azzafranty; Anisa Mirsa Bintari Putri; Jessica Estrella Maya Doko (Nexus Publishing NXP, 2025)
The purpose of this study is to identify the context that affects meaning, especially the meaning of idioms in German, which is expected to help improve understanding in cross-cultural communication skills between languages. Communication is an important part that is done by humans as social beings in order to fulfill their needs. It involves not only the transfer of words but also the exchange of cultural values, emotions, and intentions. Throughout the communication process, there are several errors in conveying information due to inaccurate interpretation of meaning. Misunderstandings often arise when idiomatic expressions are interpreted literally, rather than contextually, especially by language learners. Besides, this study answers three main research questions: how to understand the context of meaning in German idiom expressions; what is the function and role of idiom meaning (Redewendungen); and are there any relationships between idioms and cultural contexts. By using qualitative research methods such as media analysis, on the YouTube platform, this study aims to gather insights into idioms used in daily German communication. Analyzing idioms through authentic media content provides a more realistic and culturally grounded understanding of how they are actually used. It also helps highlight the connection between language use and cultural perception in real-life situations.